Sequential bioaugmentation of the dominant microorganisms to improve the fermentation and flavor of cereal vinegar - Ao Zhang; Wenqing Zhang; Xiaorui Guo; Jiao Wang; Kai Liang; Yaao Zhou; Fanfan Lang; Yu Zheng; Min Wang (Food Chemistry: X)
Traditional cereal vinegars are fermented by microorganisms that are spontaneously enriched, leading to uncertainty in regulating the fermentation process and flavor. The objective of this study was to elucidate the impact of the predominant microorganisms, provenly Lactobacillus helveticus and Acetobacter pasteurianus, on the solid-state fermentation (SSF) and flavor profile of cereal vinegar by several bioaugmentation strategies. The results indicated that the sequential bioaugmentation of predominant microorganisms improved the utilization of raw material and most key flavor compounds. Through sequential bioaugmentation strategy, bacterial diversity was regulated due to minimizing acetic acid inhibition in the early stages, and the non-volatile acid was targetedly improved by Lactobacillus. Furthermore, the important flavor of non-volatile acid, esters, acetoin, and tetramethyl-pyrazine content was enhanced by sequential bioaugmentation. Therefore, the sensory score on taste and odor were improved. These results provide a reference for the targeted regulation of the SSF and the flavor quality of cereal vinegar.